2003
DOI: 10.17221/4092-pse
|View full text |Cite
|
Sign up to set email alerts
|

Earliness, spike productivity and protein content in European winter wheat landraces and obsolete cultivars

Abstract: European winter wheat landraces and obsolete cultivars (121 accessions in set I and 101 accessions in set II) with modern check cultivars were evaluated in three-year field trials. Increased spike productivity in modern cultivars could be attributed mainly to increased number of grains in spikelet and increased HI, whereas TGW has marginal effect. Old cultivars had on average by 2-3% higher crude protein content in grain than modern ones. Among selected 10 characters, relatively wide diversity (C.V. 11-20%) ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 10 publications
(7 reference statements)
3
8
0
Order By: Relevance
“…The main and sub groups diversity in two different districts is due to high diverse genetic makeup of guava accessions (SINGH and BAINS, 1968). Similar results were observed by Walia and Garg (1996), Mehmood et al (2016) and Dotlacil et al (2000) who indicated a nonparallelization between geographic effects and genetic diversity. Unexpectedly, the accessions 'Gola and Surahi' showed the same genotype, which can be explained by the dissemination of seeds of the same accessions throughout these districts in the past.…”
Section: Dna Polymorphism Generated By 18 Ssr Primers and Phylogenetisupporting
confidence: 89%
“…The main and sub groups diversity in two different districts is due to high diverse genetic makeup of guava accessions (SINGH and BAINS, 1968). Similar results were observed by Walia and Garg (1996), Mehmood et al (2016) and Dotlacil et al (2000) who indicated a nonparallelization between geographic effects and genetic diversity. Unexpectedly, the accessions 'Gola and Surahi' showed the same genotype, which can be explained by the dissemination of seeds of the same accessions throughout these districts in the past.…”
Section: Dna Polymorphism Generated By 18 Ssr Primers and Phylogenetisupporting
confidence: 89%
“…sharonensis accessions (Table 5), as all of them exhibited a CV value >10%. Dotlacil et al (2000) considered a minimum CV value of 10% as an indication of wide morphologic diversity in wheat landraces and obsolete varieties. The highest level of diversity in Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, however, other crops were important at the Czech territory -pseudocereals and cereals, mainly buckwheat, millet and some neglected wheat species (spelt wheat, emmer wheat and einkorn wheat). Although most local landraces were lost in the last century, some valuable local materials still exist and they should be conserved (some of them preferably in "on farm") and effectively utilised to increase the agrobiodiversity in field cropping systems (DOTLAČIL et al , 2000a. All above-mentioned species provide specific quality products, which can be utilised in human nutrition.…”
Section: Evaluation and Utilisation Of Neglected Cropsmentioning
confidence: 99%